Development of Limited Liability Companies after the Enactment of Law Number 6 of 2023 Concerning the Ratification of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation - Yunus, Muhammad; Setiady, Tri (Universitas Muhammadiyah Tangerang, 2024)
This study aims to analyze the development of limited liability companies (LLCs) following the enactment of Law Number 6 of 2023, which ratifies Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation, and to explore the concept of The Private Individual Limited Company in Indonesia. The research employs a qualitative methodology, using a normative legal approach. The findings indicate that the Job Creation Law introduced a new legal entity, The Private Individual Limited Company, and altered the conventional paradigm of LLCs. Previously, LLCs were understood as capital partnerships requiring at least two founders, formed through an agreement. However, under the new law, LLCs can now be established by a single individual, provided the company qualifies as a micro, small, or medium enterprise (MSME). The concept of The Private Individual Limited Company allows a single person to establish an LLC, expanding the traditional understanding of LLCs as partnerships formed through agreements. However, this concept of single-person LLCs is not entirely new in Indonesia. Before the Job Creation Law, the Company Law (PT Law) already permitted such exceptions, allowing LLCs to be established by one person if the company’s shares were wholly owned by the state, state-owned enterprises, or regional government-owned enterprises.